2022
DOI: 10.3390/diagnostics12061477
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy across Dense and Non-Dense Breasts during Digital Breast Tomosynthesis and Ultrasound Assessment for Recalled Women

Abstract: Background: To compare the diagnostic efficacy of digital breast tomosynthesis (DBT) and ultrasound across breast densities in women recalled for assessment. Methods: A total of 482 women recalled for assessment from January 2017 to December 2019 were selected for the study. Women met the inclusion criteria if they had undergone DBT, ultrasound and had confirmed biopsy results. We calculated sensitivity, specificity, PPV, and AUC for DBT and ultrasound. Results: In dense breasts, DBT showed significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…3 ). One study [ 20 ] reported a higher sensitivity of DBT (98.2 %, 95 % CI 94.8−99.6 %) than US (80.0 %, 95 % CI 73.0−85.6 %); another [ 23 ] reported a sensitivity of 100 % for both modalities. The specificity of DBT in recalled cohorts ranged from 15.4 % to 96.0 %, with US ranging from 55 % to 100 % ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 ). One study [ 20 ] reported a higher sensitivity of DBT (98.2 %, 95 % CI 94.8−99.6 %) than US (80.0 %, 95 % CI 73.0−85.6 %); another [ 23 ] reported a sensitivity of 100 % for both modalities. The specificity of DBT in recalled cohorts ranged from 15.4 % to 96.0 %, with US ranging from 55 % to 100 % ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While one study did not find a difference between the specificities [ 13 ], two studies reported conflicting results—the specificity of DBT was lower than US in one study (15.4 %, 95 % C.I. 9.6–23.0 % versus 55 %, 95 % CI 44.8−63.0 %) [ 20 ], but higher than US in another (81.3 % 95 % CI 71.8−88.7 % versus 53.9 %, 95 % CI 43.1−64.4 %) [ 23 ]. One study included mixed cohorts (symptomatic and recalled patients); but did not report differences between sensitivity or specificity of DBT versus DM (86 % versus 97 % and 81 % versus 85 %, respectively) [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations